Russian institution of bankruptcy under its legal transformation - O. A. Lvova (Russian Journal of Economics and Law)
Objective: to systematically study the development of modern Russian legislation on insolvency (bankruptcy) in order to identify the features of evolution, evaluate the results, and identify promising areas for the transformation of the bankruptcy system. Methods: the study used general scientific methods of cognition, including a systematic approach, analysis and synthesis, logical and comparative analysis, the method of grouping and generalization, expert analysis, methods of scientific classification, tabular and graphical methods of data visualization.Results: the principles and methodological approaches to the analysis of the effectiveness of transformational processes in the field of bankruptcy were developed; 118 versions of the law that made 1,604 changes over 18 years were studied; the annual frequency, volume and nature of changes, and the adaptation period were determined; on that basis, the absence of correlation was revealed between the number of changes and the intensity of company bankruptcies; the main elements of the modification of the conceptual apparatus were identified; the dominant vector for strengthening the creditors’ rights and the debtor’s responsibility while maintaining the relative limitation of their rights was confirmed; the rare nature of changes in rehabilitation procedures and the low effectiveness of the bidding system were revealed; the process of institutionalization of arbitration managers and self-regulatory organizations was shown; the high adaptability of the institution of bankruptcy of certain categories of debtors was confirmed; the noticeable results of the information component development were reflected; the expediency of using a systematic approach to the subsequent modernization of bankruptcy was justified.Scientific novelty: for the first time, a comprehensive in-depth study of the process of reforming the modern insolvency law was conducted, based on the developed algorithm of chronological and horizontal (content) analysis for quantitative and qualitative assessment of the results of changes according to the ten proposed vectors.Practical significance: the main provisions and conclusions of the scientific work can be used: a) in scientific activities for the further development of the methodological apparatus of bankruptcy research; b) by legislative bodies in the preparation of draft normative-legal acts in order to improve the bankruptcy system in Russia; c) in law enforcement practice when the parties consider the feasibility of bankruptcy procedures, taking into account the identified opportunities and limitations.